The combination of reprimand techniques and psycho-religious therapy (dzikir) on the ability to control auditory hallucinations in patients with schizophrenia - Sindi Novitasari; Aulia Rahman; Sujiah Sujiah (JOURNAL OF Mental Health Concerns, 2026)
Background: Schizophrenia is one of the mental disorders characterized by positive psychotic symptoms, such as hallucinations, delusions, disorganized speech, and disorganized or catatonic behaviour. It was recorded that 40.5% of patients experience these symptoms, which, if left untreated, can trigger violent behaviour. Purpose: To determine the effect of the combination of reprimanding techniques and psych religious therapy (dhikr) on the ability to control auditory hallucinations in schizophrenia patients. Method: A quantitative method with a Quasi-Experimental design thru a Two Group Pretest-Posttest with Control Group approach. The sample consisted of 30 respondents selected thru purposive sampling. The research instrument used the Auditory Hallucination Rating Scale (AHRS) observation sheet to assess the level of hallucinations before and after the intervention. Results: The average hallucination score of the intervention group significantly decreased from 38.53 (very severe) to 29.27 (severe). Statistical tests showed a p-value of 0.000 (< 0.05), which means there is a significant effect of the combination of reprimanding techniques and dhikr on the ability to control hallucinations. Conclusion: The combination of reprimanding techniques and dhikr is effective in improving the ability to control auditory hallucinations. The recommendation in this study is for health institutions to implement this therapy as a standard for comprehensive mental health nursing care. Keywords: Auditory Hallucinations; Dhikr; Schizophrenia; Scolding Technique.